Design and Simulation of an Antenna-Coupled Microbolometer at 30 THz - Colín, Ángel; Pérez Tijerina, Eduardo Gerardo; Solís Pomar, Francisco (Herve Aubert, 2017)
Weproposeamodelofantenna-coupledmicrobolometertobeincludedinanarrayforreceivinganddetectinglongwaveinfrared (LWIR) electromagnetic radiation. The antenna is joined to microstrip bandpass filters thus forming a single metal structure to definetheoperationfrequencyband.Theantennaandmicrostripfiltersaremodeledinaluminumthinfilm.Themicrobolometer ismodeledwithsuperconductingniobium,alltogetheronasiliconnitridemembrane.Thesquaredpixelstructureisdesignedon asupportframeof20